A type-logical treebank for French - Moot, Richard (Journal of Language Modelling, 2015)
The goal of the current paper is to describe the TLGbank, a treebank of type-logical proof semi-automatically extracted from the French Treebank. Though the framework chosen for the treebank are multimodal type-logical grammars, we have ensured that the analysis is compatible with other mondern type-logical grammars, such the displacement calculus and first-order linear logic. We describe the extraction procedure, analyse first results and compare the treebank to the CCGbank.